Contract law rules, theory, and context - Bix, Brian (Cambridge Cambridge University Press, 2012)
"This book offers an accessible introduction to all aspects of American contract law, useful to both first-year law students and advanced contract scholars"-- Provided by publisher.
"Contract law is a category within legal practice (and legal education), though there are many occasions where there are significant overlaps with other categories, or where the borderline is not especially clear. (For example, some commentators have argued that contract law should be seen as a mere sub-category of tort law ; and, in different ways, the boundary lines between contract law and areas like restitution and property are fluid and uncertain much of the time.) Contract law is a category of particular rules and decisions, but (as elsewhere in law) it is a mistake to focus too narrowly on the "facts" of the actual decisions and the "black-letter rules" of treatises. Law is, and likely has always been, a reflective exercise, where there is a natural tendency (among practitioners and observers both) to seek more general principles, to explain and justify past decisions and give guidance for future decisions"-- Provided by publisher.
Machine generated contents note: 1. Philosophical problems of contract law; 2. History and sources; 3. Formation; 4. Interpretation; 5. Performance; 6. Enforcement and remedies; 7. Special categories of contract law; 8. Modern contract law practices: questions of legitimation; 9. How many contract laws?.
Keywords: Contracts -- United States